The Effect of Fixed Asset Administration With ATISISBADA, and Human Resource Competencies on the Quality of SKPD Financial Reports - Saepul Hayat, Usep; Silviana, Silviana (DINASTI RESEARCH, 2025)
This research aims to look at the effect of fixed asset administration with the Regional Goods Cycle Information Technology Application (ATISISBADA) and human resource competencies on the quality of financial reports at the Garut Regency Government in 2023. This type of research uses descriptive verification. Data was collected by distributing questionnaires to the entire population of 75 Regional Apparatus in the Garut Regency Government. Hypothesis testing in this study used multiple linear regression analysis. The results showed that the administration of fixed assets with the Regional Goods Cycle Information Technology Application and the competence of human resources had a significant effect on the quality of financial reports of the Garut Regency Government Regional Apparatus.